Development of an andragogical model for optimizing di-dactic competencies in the public sector - Montes, Mercedes Fatima Benites; Vera, Juan Raúl Egoavil (Edelweiss Applied Science and Technology, 2025)
The importance of the andragogical approach plays a fundamental role in the realm of profes-sional training, particularly in the public sector, emphasizing the improvement of the didactic competencies of trainers according to their employment regime. This research aimed to estab-lish the relationship between the andragogical approach and the optimization of didactic compe-tencies among professionals at a training center belonging to a public entity in Peru. The study was conducted with a sample of 120 public sector trainers, employing a quantitative, non-experimental, cross-sectional research design with a correlational scope. Questionnaires were used to collect data, which were analyzed using the Spearman Rho test, yielding a correlation coefficient of r = 0.529 and a significance level of 0.002. These results allowed for the rejection of the null hypothesis and confirmed the hypothesis that the andragogical approach has a signifi-cant impact on improving didactic competencies. The instruments used to measure the variables showed high reliability, with Cronbach's alpha coefficients of 0.890 and 0.873 for the andragogi-cal approach and didactic competencies, respectively. It was concluded that implementing an ef-fective andragogical approach can significantly contribute to strengthening professional compe-tencies, creating an enriching and efficient training environment for trainers in the public sector, depending on the developed model and context.